Evaluation of myocardial damage in different types of rheumatoid arthritisduring disease-modifying antirheumatic drug or biological therapy (with infliximab) - V I Mazurov; Andrey Valentinovich Kol'tsov; M M Toporkov; V A Kachnov; E N Tsygan; V V Tyrenko; T E Trufanov; I S Zheleznyak; A E Nikitin; S V Dolgikh; Yu B Shul'man; V I Mazurov; et al. (Научно-практическая ревматология, 2010)
Objective. To estimate the extent and pattern of myocardial damage in different types of rheumatoid arthritis (RA) during disease-modifying antirheumatic drug (DMARD) or biological therapy. Subjects and methods. Seventy-one patients with RA were examined; some of them received biological therapy with infliximab, while the others took DMARDs. A group of patients with incipient RA was also identified. B-type brain natriuretic peptide levels were estimated and electrocardiography, echocardiography (EchoCG), and cardiac magnetic resonance imaging (MRT) using the contrast medium Dotarem were conducted in all the patients. The follow-up totaled 6 months. A control examination was made at the moment of randomization and 6 months posttreatment. Results. Tn the bulk of patients, the level of B-type brain natriuretic peptide did not differ from the reference values, however, its lower level was observed in the incipient RA group, which was associated with the absence of cardiovascular diseases and with a younger age group. There were no negative EchoCG changes in myocardial viability values. Cardiac MRT demonstrated that the majority of patients had the similar changes that failed to affect myocardial kinetics and ejection fraction. These changes were not found in incipient RA patients without cardiovascular diseases. No improvement in myocardial viability was recorded in the patients receiving the biological therapy. Conclusion. Thus, cardiac MRT showed the similar changes that failed to affect myocardial kinetics and ejection fraction in patients with RA during both methotrexate and infliximab therapy.